Bekeringsverhalen: aansluiten bij, betrokken zijn bij, en afscheid nemen van de nieuwe religieuze beweging Uit de Bron van Christus - Jansma, Lammert Gosse (Religie & Samenleving, 2014)
In the debate on religious conversion it has been often stated that conversion stories are not factual accounts but interpretations in retrospect of the convert’s biography, which he has rewritten after the way the (ideal) conversion is depicted in the doctrine of the group he has joined. Is the rewriting a continuous affair or does it stop when the conversion has been fashioned after the way the religious group prescribes? In the article we present data on the prophetic healing movement ‘Uit de Bron van Christus’ (From the Source of Christ) to give insight into how converts describe their conversion process and if reinterpretation does end after accepting the conversion model of the movement.